2012
DOI: 10.1002/job.1807
|View full text |Cite
|
Sign up to set email alerts
|

Shared aggression concerns and organizational outcomes: The moderating role of resource constraints

Abstract: Summary Most research on workplace aggression focuses on the antecedents and consequences of aggression for individual workers. The current study examines how shared workplace aggression concerns relate to internal and external organizational outcomes. Drawing on the work stress, social identity, and social contagion literatures, we propose relationships between unit‐level aggression concerns and unit‐level measures of performance and employee attitudes in a public school sample (2989 employees; 163 schools). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…Focusing on the role of co-workers’ interactions could be beneficial to the school sector to prevent incivility from escalating into more aggressive forms of mistreatment. This is in line with previous research (Wittmer, Sinclair, Martin, Tucker, & Lang, 2013 ) suggesting a prevention-focused approach to reduce workplace aggression in educational environments. Wittmer et al ( 2013 ) found that workplace aggression has adverse consequences, not only for the affected individuals, but for the entire organization, showing the importance of approaching workplace incivility at an early stage in order to prevent a culture of uncivil behaviour from being developed.…”
Section: Discussionsupporting
confidence: 92%
“…Focusing on the role of co-workers’ interactions could be beneficial to the school sector to prevent incivility from escalating into more aggressive forms of mistreatment. This is in line with previous research (Wittmer, Sinclair, Martin, Tucker, & Lang, 2013 ) suggesting a prevention-focused approach to reduce workplace aggression in educational environments. Wittmer et al ( 2013 ) found that workplace aggression has adverse consequences, not only for the affected individuals, but for the entire organization, showing the importance of approaching workplace incivility at an early stage in order to prevent a culture of uncivil behaviour from being developed.…”
Section: Discussionsupporting
confidence: 92%
“…While the typical source of teacher-targeted violence is students, teachers can also experience aggression from their colleagues or the students’ parents 10. Teacher victimisation has been shown to be associated with poor job attitudes and professional disengagement,11 which may result in reduced learning outcomes in the classroom 12. Furthermore, studies have linked violence towards teachers to adverse health outcomes commonly associated with occupational stress, such as poor emotional and psychosomatic well-being 4.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to wanting to prevent bad things from happening, psychologists also want to know what can be done to ameliorate the effects when bad things do happen. For example, Wittmer, Sinclair, Martin, Tucker, and Lang (2013) assess the role of shared employee concerns about aggression in their schools as a precursor to lower student level performance (test scores) and more negative unit level attitudes toward working conditions. The authors argue that school resources moderate this relationship.…”
Section: Buffering Rv Interactions In Workplace Mistreatmentmentioning
confidence: 99%